Suitable additives for vegetable oil‐based automotive shock absorber fluids: an overview. (22nd March 2016) - Bongfa, Binfa; Syahrullail, S.; Abdul Hamid, M. K.; Samin, P. M.
Abstract: Formulation of a cost‐effective, high‐performance and eco‐friendly lubricant, largely depends on the base oil quality, then the selection of suitable additives and their proportions. Vegetable oils, identified to be eco‐friendly, renewable, future‐available and cost‐effective treasures for lubricant formulation, apart from processing, will rely much on suitable additives to meet the performance requirements for automotive shock absorber (ASA) fluids. Additives that will guarantee performance, longevity and eco‐friendliness of formulated vegetable‐based functional fluids have to be uncommonly effective, resistant to depletion, non‐toxic and highly biodegradable. Their selection in these regards will require skills and experience, which will harness the various arms of synergism as effective tools to succour the known weaknesses of the base oil. This is a review on additives that could be used in formulation of vegetable oil‐based (ASA) fluids. The outcome shows that there are customary and novel additives that are suitable for formulating vegetable oil‐based ASA fluids. Copyright © 2016 John Wiley & Sons, Ltd.